2023
DOI: 10.1101/2023.07.17.549401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fragment ion intensity prediction improves the identification rate of non-tryptic peptides in timsTOF

Abstract: Immunopeptidomics plays a crucial role in identifying targets for immunotherapy and vaccine development. Because the generation of immunopeptides from their parent proteins does not adhere to clear-cut rules, rather than being able to use known digestion patterns, every possible protein subsequence within HLA class-specific length restrictions needs to be considered. This leads to an inflation of the search space and results in lower spectrum annotation rates. Rescoring is a powerful enhancement of standard se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Application of DeepNovo Peptidome to expand the reference HLA Ligand Atlas of benign human tissues As neoantigens mostly arise from non-canonical sources which are challenging for standard database search approaches, we built DeepNovo Peptidome, a de novo sequencing-based workflow for HLA peptide identification and neoantigen discovery. We trained the de novo sequencing model 13,14 on a very large, carefully curated dataset from 20 previous MS-based immunopeptidomics studies 5,15,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . The dataset included nearly 3,000 runs on two major MS instruments Orbitrap and timsTOF, >26M PSMs and >1.1M unique HLA peptides, and covering more than 90 alleles for each HLA class.…”
Section: Resultsmentioning
confidence: 99%
“…Application of DeepNovo Peptidome to expand the reference HLA Ligand Atlas of benign human tissues As neoantigens mostly arise from non-canonical sources which are challenging for standard database search approaches, we built DeepNovo Peptidome, a de novo sequencing-based workflow for HLA peptide identification and neoantigen discovery. We trained the de novo sequencing model 13,14 on a very large, carefully curated dataset from 20 previous MS-based immunopeptidomics studies 5,15,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . The dataset included nearly 3,000 runs on two major MS instruments Orbitrap and timsTOF, >26M PSMs and >1.1M unique HLA peptides, and covering more than 90 alleles for each HLA class.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the previously used metrics, mass to charge ration (m/z), retention time (RT) and IM, the additional metrics, such as predicted spectral angle (SA) and the predicted RT, have been introduced to enhance the (immune)peptide identification. 57 , 58 , 59 These synergic progresses both in MS hardware and the supportive search systems make robust identification possible from the growing large‐scale MS raw data. As handling of gigantic MS data has become more generalized, machine‐learned search‐assisting algorithms play a greater role in this field.…”
Section: Transformative Technologies That Shed Light Upon the Dark Ma...mentioning
confidence: 99%
“…We, and others, have previously shown that different fragmentation methods can heavily alter peptide MS2 spectra (27,28). We therefore trained new MS²PIP models that can accurately predict peak intensities for timsTOF acquired peptides.…”
Section: Ms²pip Prediction Modelsmentioning
confidence: 99%